Classification of vigor levels for soybean seeds using the accelerated aging test - Thaisa Cavalieri Matera; Francisco Carlos Krzyzanowski; Alessandro Lucca Braccini; Carlos Alberto Scapim (Journal of Seed Science)
ABSTRACT: The accelerated aging test is among the most widely used seed vigor tests, due to its accuracy and sensitivity in detecting differences in physiological quality among seed lots with similar germination rates. Thus, the objective of this study was to develop a soybean seed vigor classification table for the period of seed delivery to customers after six months of conventional storage using the results obtained in the accelerated aging test at 41 °C for 24 hours. For that purpose, regression equations were used, considering the vigor level results from the accelerated aging test as the independent variable and the germination test, first germination count, seedling vigor classification, electrical conductivity, and percentage of seedling emergence in the field as dependent variables. Their relationships with seed physiological quality were estimated using Pearson’s simple correlation analysis and simple regression analysis at 1% and 5% probability levels. The vigor classification levels for soybean seeds after the accelerated aging test are proposed as follows: very high (90% to 100% normal seedlings), high (80% to 89% normal seedlings), medium (61% to 79% normal seedlings), and low (≤ 60% normal seedlings).